Review of Tax Coverage in Digital Insurance Companies PT XYZ Case Study - Ameliyaningsih, Tri; Shafina, Evelyne; Pahala, Indra; Wahono, Puji (Transpublika Publisher, 2025)
The rapid growth of digital insurance companies, such as PT XYZ, presents new challenges in taxation due to the technology-based nature of their operations. This research aims to examine the application of tax policies, specifically Corporate Income Tax (CIT), Value Added Tax (VAT), and Income Tax Article 21 (ITA 21) at PT XYZ. This research uses a qualitative approach with a case study method, which collects data through interviews with company management and analyzes secondary data, including financial statements and tax documents. The results showed a gap between the prevailing tax policy and the operational reality of digital insurance companies, especially in digital revenue recognition and the application of VAT on insurance products sold online. PT XYZ faces challenges in reconciling salary costs due to the company's policy of capitalizing employee compensation. This study concludes that tax regulations need to be adjusted to better suit the characteristics of the digital insurance business. The results suggest that regulators should consider revising tax policies to address these challenges, in order to achieve tax efficiency without sacrificing compliance.